Renal Transplantation into a Diverted Urinary System—Is it Safe in Children? - Christman, Matthew S; Canning, Douglas A; Schast, Aileen P; Baluarte, H. Jorge; Kaplan, Bernard S (The Journal of urology, 2013)
Purpose Historically surgeons caring for children with urinary diversion for bladder outlet obstruction have routinely performed undiversion before renal transplantation. We hypothesized that patients undergoing transplantation into a diverted system would have outcomes similar to those undergoing transplantation into a normal bladder. We review the outcomes of patients with and without diversion undergoing kidney transplantation at our institution. Materials and Methods We retrospectively studied a cohort of children undergoing renal transplant between 1993 and 2006. Patients whose etiology of end-stage renal disease was either obstructive uropathy or renal dysplasia were included. Patients with less than 5 years of followup were excluded from the analysis. Four groups were assembled, ie controls with renal dysplasia and no history of obstructive uropathy undergoing transplant (group 1), patients with obstructive uropathy not diverted at transplant (group 2), patients with obstructive uropathy diverted at transplant (group 3) and patients with obstructive uropathy augmented before transplant (group 4). The groups were compared for outcomes of frequency of urinary tract infection, renal graft function and graft loss. Results Of the 80 subjects eligible based on diagnostic criteria 43 had completed 5 years of followup. There was no significant difference between groups based on age (p = 0.508), renal function as measured by glomerular filtration rate (p = 0.526) or creatinine (p = 0.612), or frequency of urinary tract infections (p = 0.083). Only 1 patient in the cohort suffered graft loss. Conclusions Based on frequency of urinary tract infection, renal function and graft loss 5 years after transplant, there appears to be no added risk to transplanting a kidney into a diverted system.